Electrical Properties of Nafion 117 Membrane at Variable Temperatures and Solution Uptakes - Raja Mustapha, Raja Ibrahim Putera (2011)
Nafion being among the best proton exchange membrane for the use of Fuel Cell was studied to find the best parameters to be used to increase conductivity. Currently Nafion exhibits high rates of methanol crossover in the application of Direct Methanol Fuel Cell which occurs at high pressure and high temperature that lowers the power output of the system. This work studies the Nafion membrane at relatively low temperatures up to the boiling point of methanol (28oC to 65oC) and at atmospheric pressure. Nafion membrane is investigated when it is dry, in deionized water, pure methanol, pure ethanol and in different solution ratios of deionized water to methanol (1:3, 1:1, 3:1) and different solution ratios of deionized water to ethanol (1:3, 1:1, 3:1). Nafion is also observed at different solution uptakes, first being at fully saturated, at 5% solution uptake and at 10% solution uptake. The main interest in this study to optimize power output is to look into the conductivity values obtained from the given environments. It was observed that conductivity increases with increasing thickness of the membrane as a result of absorption of the solution introduced where the best obtained values for alternating current conductivity is obtained for Nafion in 50% methanol and 50% ethanol solutions. While for the direct current conductivity, the best was obtained at 75% methanol and 75% ethanol solutions. From other studies, Nafion’s conductivity was supposed to increase with increasing water content but here the opposite is true because deionized water was used where all the impurities usually present in water is discarded as well as the fractionation effect. The results obtained were attributed to proton tunneling mechanism and also plasticization effect of alcohol on the membrane. For Nafion at room temperature, the ac conductivity when dry, in deionized water, pure methanol and pure ethanol were in the range of 3.12 × 10-8 - 1.52 × 10-4 S m-1, 2.76 × 10-5 - 6.33 × 10-3 S m-1, 6.83 × 10-6 - 6.92 × 10-3 S m-1 and 1.05 × 10-5 – 4.74 × 10-3 S m-1 respectively. While for dc conductivity for Nafion when dry, in deionized water, pure methanol and pure ethanol were in the range of 4.31 × 10-4 – 5.90 x 10-4 S m-1, 1.14 x 10-2 – 1.72x10-2 S m-1, 1.36 x 10-3 – 1.87 x 10-3 S m-1 and 7.20 x 10-4 – 8.82 x 10-4 S m-1 respectively. Whereas for the conduction activation energy of Nafion when dry, in deionized water, pure methanol and pure ethanol were 5.72 x 10-1 eV, 1.06 eV, 1.05 eV and 2.32 eV respectively. With the thickness being the difference between the 5%, 10% and fully saturated Nafion membrane, the conductivity from fully saturated to 5% solution uptake shows a 53-96% decrease. While from fully saturated to 10% solution uptake shows a 71-98% decrease. The conduction activation energy for the 5% solution uptake is 52-98% less than for the saturated membrane. And for the membrane with 10% solution uptake is 68-81% less.